2014
DOI: 10.1007/s00247-014-3149-z
|View full text |Cite
|
Sign up to set email alerts
|

Shear wave elastography helps differentiate biliary atresia from other neonatal/infantile liver diseases

Abstract: Liver shear wave speed is abnormally increased in neonates and infants with biliary atresia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
66
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 71 publications
(70 citation statements)
references
References 29 publications
1
66
0
Order By: Relevance
“…We obtained parental/guardian informed consent for all study participants; we obtained subject assent for children older than 10 years. Some data from 11 children in this investigation were previously presented in a recent study that used shear wave elastography to help differentiate biliary atresia from other causes of neonatal/infantile jaundice [12].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…We obtained parental/guardian informed consent for all study participants; we obtained subject assent for children older than 10 years. Some data from 11 children in this investigation were previously presented in a recent study that used shear wave elastography to help differentiate biliary atresia from other causes of neonatal/infantile jaundice [12].…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, US shear wave elastography is a portable technique that can allow imaging in the radiology department or clinic and at the bedside. To date, a relatively small number of studies have evaluated the use of US shear wave elastography for detecting liver fibrosis in children [11][12][13][14][15]. Acoustic radiation force impulse (ARFI) SWE techniques use US force to generate transient tissue deformations that give rise to in vivo shear waves in an organ of interest (e.g., liver).…”
Section: Introductionmentioning
confidence: 99%
“…Liver biopsy is not very well accepted by the parents of children with chronic hepatitis and it is difficult to use it during the follow-up in case of paediatric patients. There is a trend towards replacing liver biopsy by elastography for the evaluation of liver fibrosis among children with chronic diffuse liver diseases [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…The mean shear wave speed was found to be significantly higher in children with biliary atresia as compared to those with other causes of cholestasis. The pSWE technique found a mean velocity of 2.08 m/s in biliary atresia compared to 1.28 m/s in other causes of cholestasis, and the 2D SWE technique found a mean velocity of 3.14 m/s in biliary atresia compared to 1.61 m/s in other causes of cholestasis (32). TE significantly correlates with histologic fibrosis staging in children with biliary atresia.…”
Section: Biliary Atresiamentioning
confidence: 81%
“…Traditionally, ultrasound is used to evaluate for biliary atresia looking for indicators of disease such as absent or irregular gallbladder, absent common bile duct and presence of an echogenic triangular cord above the porta hepatis. Leschied et al (32) found that pSWE can differentiate biliary atresia from other neonatal liver diseases that have a similar clinical presentation such as neonatal hepatitis and Alagille syndrome. The mean shear wave speed was found to be significantly higher in children with biliary atresia as compared to those with other causes of cholestasis.…”
Section: Biliary Atresiamentioning
confidence: 99%